PENGARUH LINGKUNGAN KERJA, PELATIHAN KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI SUKU DINAS TENAGA KERJA, TRANSMIGRASI, DAN ENERGI KOTA ADMINISTRASI JAKARTA TIMUR - Calvin Bangun David (2023)
This research is a quantitative study aimed at investigating the impact of work environment, training, and work discipline on employee performance in the Regional Office of Manpower, Transmigration, and Energy of East Jakarta Administrative City. The study involved 32 respondents who were permanent employees with the same tasks and responsibilities within the organization. Data were collected through questionnaire distribution. The statistical analysis method used was Partial Least Square (PLS), specifically SmartPLS 3.0, to test hypotheses partially (T) and simultaneously (F). The findings of this study are as follows: (1) work environment has a positive and significant influence on employee performance, (2) training has a positive and significant influence on employee performance, (3) work discipline has a positive and significant influence on employee performance, and (4) collectively, work environment, training, and work discipline have a significant influence on employee performance in the Regional Office of Manpower, Transmigration, and Energy of East Jakarta Administrative City.